Embryo - "George, Robert P."; "Tollefsen, Christopher." (New York)
Includes bibliographical references (p. 219-231) and index. What is at stake in the embryo experimentation debate -- The facts of embryology -- Dualism and persons -- Moral philosophy and the early human being -- Moral dualism -- New objections to the humanity of the early embryo -- Further challenges.
Keywords: EMBRYONIC STEM CELLS -- MORAL AND ETHICAL ASPECTS;HUMAN EMBRYO -- RESEARCH -- MORAL AND ETHICAL